Glutathione transferase theta in apical ciliary tuft regulates mechanical reception and swimming behavior of Sea Urchin Embryos. Issue 8 (19th August 2013) - Jin, Yinhua; Yaguchi, Shunsuke; Shiba, Kogiku; Yamada, Lixy; Yaguchi, Junko; Shibata, Daisuke; Sawada, Hitoshi; Inaba, Kazuo
<x xml:space="preserve">Abstract</x> An apical tuft, which is observed in a wide range of embryos/larvae of marine invertebrates, is composed of a group of cilia that are longer and less motile than the abundant lateral cilia covering the rest of the embryonic surface. Although the apical tuft has been thought to function as a sensory organ, its molecular composition and roles are poorly understood. Here, we identified a glutathione transferase theta (GSTT) as an abundant and specific component of the apical tuft in sea urchin embryos. The expression of GSTT mRNA increases and becomes limited to the animal plate of the mesenchyme blastula, gastrula, and prism larva. Electron microscopy and tandem mass spectrometry demonstrated that the apical tuft contains almost every axonemal component for ciliary motility. Low concentrations of an inhibitor of glutathione transferase bromosulphophthalein (BSP) induce bending of apical tuft, suggesting that GSTT regulates motility of apical tuft cilia. Embryos treated with BSP swim with normal velocity and trajectories but show less efficiency of changing direction when they collide with an object. These results suggest that GSTT in the apical tuft plays an important role in the mechanical reception for the motility regulation of lateral motile cilia in sea urchin embryos. © 2013 Wiley Periodicals, Inc.